Early Changes in Saccadic Eye Movement in Hemiparkinsonian MPTP-Treated Monkeys. (August 2015) - Tereshchenko, Leonid V.; Anisimov, Victor N.; Shul'govsky, Valery V.; Latanov, Alexander V.
The saccadic eye movements declining given the development of Parkinson's disease (PD) still deserves thorough analysis. Recent studies confirmed that PD patients show poor saccadic control in visuomotor tasks. The purpose of this study was to investigate the dynamics of saccades parameters at the development of 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) model of PD. The gradual decline of saccadic control was studied in two monkeys that executed the visuomotor task with low doses of MPTP being injected at a prolonged period of time. The experiment included investigating the horizontal, vertical, oblique visually guided saccades as well as the corrective saccades triggered by stimuli onset in various loci within a two-dimensional visual field in the Gap-Step-Overlap paradigm. Our study revealed that the execution of visually guided saccades with small amplitude and corrective saccades changed dramatically with MPTP-model progressing. These changes are also confirmed statistically at the presymptomatic stage of MPTP syndrome. Not only our study gives a robust report of PD dynamics development and saccadic control but the obtained data could also be helpful in developing methods for the early diagnosis of PD.